2009
DOI: 10.4028/www.scientific.net/msf.618-619.155
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry Control in Electron Beam Deposited Titanium Alloys

Abstract: Direct manufacturing of metallic materials has gained widespread interest in the past decade. Of the methods that are currently under evaluation, wire-fed electron beam deposition holds the most promise for producing large-scale titanium parts for aerospace applications [1]. This method provides the cleanest processing environment as the deposition is performed under vacuum. While this environment is beneficial in preventing contamination of the deposit, there is the potential for preferential vaporization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…A similar deficit in erbium content is noted. This is consistent with the loss of aluminum content due to vaporization that occurs during the electron beam additive manufacturing process that has been documented in other aluminum-bearing titanium alloys [19]. Composition values of interstitial elements, O, N, C, and H, were made only for the Ti-8Al-1Er wire feedstock and the subsequent electron deposited part.…”
Section: Methodssupporting
confidence: 86%
“…A similar deficit in erbium content is noted. This is consistent with the loss of aluminum content due to vaporization that occurs during the electron beam additive manufacturing process that has been documented in other aluminum-bearing titanium alloys [19]. Composition values of interstitial elements, O, N, C, and H, were made only for the Ti-8Al-1Er wire feedstock and the subsequent electron deposited part.…”
Section: Methodssupporting
confidence: 86%
“…When the speed was further increased (7800 mm/s), Al content decreased to 3.9 wt%. The results published by Brice et al [36] showed that the aluminum content dropped significantly also in the samples made from Ti-6Al-4V alloy processed by EBM. This is due to the fact that aluminum has higher vapor pressure than titanium and vanadium and thus vaporizes preferentially.…”
Section: Resultsmentioning
confidence: 97%
“…Most engineering alloys contain a range of alloying elements that could vaporize at high temperatures during metal AM. For example, vaporization that occurs for Al in Ti6Al4V and Mg in Al‐based alloys . The chemical composition of the final product is a key criterion that should be the same as that of the powder.…”
Section: Features Of Metal Ammentioning
confidence: 99%